Myocardial Injury in COVID-19 and Its Implications in Short- and Long-Term Outcomes - Izquierdo-Marquisá, Andrea; Cubero-Gallego, Hector; Aparisi, Álvaro; Vaquerizo, Beatriz; Ribas-Barquet, Núria (Frontiers in Cardiovascular Medicine, 2022)
COVID-19 caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is still a pandemic with high mortality and morbidity rates. Clinical manifestation is widely variable, including asymptomatic or mild respiratory tract illness to severe pneumonia and death. Myocardial injury is a significant pathogenic feature of COVID-19 and it is associated with worse in-hospital outcomes, mainly due to a higher number of hospital readmissions, with over 50% mortality. These findings suggest that myocardial injury would identify COVID-19 patients with higher risk during active infection and mid-term follow-up. Potential contributors responsible for myocardial damage are myocarditis, vasculitis, acute inflammation, type 1 and type 2 myocardial infarction. However, there are few data about cardiac sequelae and its long-term consequences. Thus, the optimal screening tool for residual cardiac sequelae, clinical follow-up, and the benefits of a specific cardiovascular therapy during the convalescent phase remains unknown. This mini-review explores the different mechanisms of myocardial injury related to COVID-19 and its short and long-term implications.